Readiness For Behavioral Change to Prevent Child Marriage Based on Individual Characteristics and Adolescent Antecedent Factors - Hikmah, Faiqatul; Kartika, Ria Chandra; Puspita, Surya Dewi; Susindra, Yoswenita; Khamid, M. Nur (International Journal of Health and Information System, 2025)
Child marriage cases place Indonesia in the seventh highest ranking in the world and are ranked second in ASEAN. Child marriage can have negative impacts both mentally and physically. Women's reproductive organs that are not ready to accept pregnancy make early marriage disrupt the reproductive health system so that it can cause various complications, especially in women. This research aims to analyze the readiness for behavioural changes in preventing child marriage based on individual characteristics and adolescent antecedents. This type of research is quantitative descriptive research with a Cross-sectional study approach. This study involved 160 teenagers aged <19 years. Individual characteristic variables, namely gender, are related to readiness for behavioural changes in preventing child marriage. Antecedent variables, namely Reproductive Health Knowledge, Parental Support and Motivation, are related to preparedness for behavioural changes in preventing child marriage. The readiness of teenagers to be able to make behavioural changes in preventing child marriage is related to individual characteristics and adolescent antecedents.